Gas sensing characteristics of the FET-type gas sensor having inkjet-printed WS2 sensing layer. (March 2019) - Jeong, Yujeong; Shin, Jongmin; Hong, Yoonki; Wu, Meile; Hong, Seongbin; Kwon, Ki Chang; Choi, Seokhoon; Lee, Taehyung; Jang, Ho Won; Lee, Jong-Ho
Highlights: The drain current of the WS2 gas sensor increases when NO2 gas is injected, but decreases when H2 S gas is injected. However, for other gases, the gas sensor has a small change of the drain current. As a result, the sensor has a high selectivity for NO2 gas. Abstract: This paper investigates the gas sensing characteristics of the MOSFET-type sensor having an inkjet-printed WS2 sensing layer. The drain current of the gas sensor increases when NO2 gas is injected into the test chamber since NO2 gas is an oxidizing gas that extracts electrons from the sensing layer. On the contrary, the drain current decreases when H2 S gas is injected into the test chamber since H2 S gas is a reducing gas that donates electrons to the sensing layer. In both cases, the change of the drain current increases as the gas concentration increases. However, for other gases (NH3 and CO2 ), the gas sensor has a small change of the drain current. The responses of the gas sensor to 10 ppm NO2, H2 S, NH3, and CO2 gases are 15.20%, 7.18%, 1.66%, and 3.02%, respectively. Therefore, the WS2 sensor has a high selectivity for NO2 gas among the four target gases.